Determinants of Prevention of Covid-19 in Communities - Wahyuni Wahyuni; Ika Silvitasari; Erika Dewi Noorratri; Sri Handayani (Indonesian Journal of Global Health Research, 2023)
The outbreak of the Covid-19 infection which is currently still spreading throughout the world has resulted. The community is making various efforts to protect themselves to avoid the Covid-19 virus which tends to attack the community respiratory tract and lungs. One effort that can be done is prevention or prevention, including hand hygiene, social distancing, using masks, and limiting mobility and staying away from crowds. This research is included in the descriptive analytic research which analyzes in the form of information or explanation related to the prevention of Covid-19. The research method with descriptive analytic analysis of univariate data with a frequency distribution of age, education, gender, occupation, income, and knowledge. This research is an analytic descriptive research in the form of a description of Covid-19 prevention. Data were obtained from questionnaires which were distributed and filled in by respondents through questionnaires as primary data. The questionnaire was not tested for validity and reliability because it only examined primary data from respondents. The number of samples is 52 people, with univariate data analysis technique. The research results obtained were that most of the respondents were aged 20-35 years as much as 42,5%. Most of the respondents were female as much as 53,8% with secondary education as much as 53,8%; Most of the respondents are self-employed as much as 26,9% and earn > UMR as much as 65,5%. Most of the respondents have high knowledge of 57,7%. The conclusion in this study is that most of them are of productive age, more female sex, more secondary education, more self-employed jobs, more income above the minimum wage, more knowledgeable respondents.